Nursery of Penaeus monodon fry in Cage Culture of Intensive Pond at Different Rearing Densities - T. Budiardi; R.D. Salleng; N.B.P. Utomo (Jurnal Akuakultur Indonesia)
Black tiger shrimp (Penaeus monodon Fab.) culture is now frequently failed as the fault in pond construction and irrigation system, disease break, and younger fry is stocking into pond.  Nursery is a rearing of PL12 to be PL25 at a controlled environmental condition to quickly adapt them on pond condition.   Nursery experiment was conducted in cage culture (1x1x1 m) placed in an intensive pond at density of 250, 500, 750 and 1000 PL/m2, for 14 days rearing.  The results of study indicated that no different in survival and growth of PL was obtained.  Daily growth rate was ranged from 1.10% to 1.53%, while the survival rate was ranged from 86.72-95.60%.  Higher production of shrimp fry (867 PL25) was obtained by rearing PL12 at density of 1000 PL/m2.